Numerical Evaluation of Tunnel Portal Slope Stability at Bagong Dam Site, East Java, Indonesia - Irien Akinina Fatkhiandari; I Gde Budi Indrawan; Dwikorita Karnawati (Geological Engineering Department Universitas Gadjah Mada, 2020)
Geometries of excavated tunnel portal slopes at Bagong Dam site was initially designed without taking into account earthquake load. The excavated slope designs also assumed the rocks consisting the slopes were homogenous. The purpose of this research was to evaluate stability of the excavated tunnel inlet and outlet slopes at the Bagong Dam site under static and earthquake loads using finite element method. Stability of the natural slopes was also analyzed for comparison. The numerical static and pseudostatic analyses of slope stability were carried out using RS2 software (Rocscience, Inc.). Input data used in the numerical analyses were obtained from engineering geological mapping, rock core analyses, and laboratory tests. Seismic coefficient applied in the pseudostatic slope stability analyses was determined following guideline described in Indonesian National Standard. The engineering geological mapping and evaluation of rock cores indicated that the inlet tunnel slope consisted of four types of materials, namely residual soil, poor quality of volcanic breccia, very poor quality of volcanic breccia, and good quality of volcanic breccia. The outlet portal slope consisted of six types of materials, namely residual soil, very poor quality of limestone, poor quality of limestone, very poor quality of volcanic breccia, poor quality breccia, and good quality breccia. Based on the secondary elastic wave velocity (Vs) values, the rock masses in the research area were classified as hard rock (SA). Seismic analyses based on the earthquake hazard source map with 10% probability of exceedance in 50 years provided by the National Earthquake Center (2017) indicated that the PGA and the corresponding amplification factor FPGA in the research area were 0.3 and 0.8, respectively. The calculated seismic coefficient for the pseudostatic slope stability analyses was 0.12. The numerical analysis results showed that, in general, earthquake load reduced critical Strength Reduction Factor (SRF) values of the slopes. However, the natural and excavated tunnel portal slopes were relatively stable under static and earthquake loads. The natural slope at the tunnel inlet with a 40° inclination had critical SRF value of 4.0, while that of at the tunnel outlet with a 51° inclination had critical SRF value of 2.6. Under static load, the excavated slopes at the tunnel inlet and outlet having a 45° inclination had critical SRF values of 2.4 and 5.0, respectively. Under earthquake load, the excavated slopes at the tunnel inlet and outlet had critical SRF values of 2.3 and 3.5, respectively.